EKSPLORASI STRATEGI PENGEMBANGAN USAHA WISATA DESA MENGGUNAKAN ANALISIS SWOT PADA ORANZ MINI WATERBOOM DESA MENDALA, KECAMATAN SIRAMPOG, KABUPATEN BREBES - Alfi Jauza Nabila; Elliv Hidayatul Lailiyah (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
This study aims to explore and formulate village tourism business development strategies using SWOT analysis at Oranz Mini Waterboom, Mendala Village, Sirampog District, Brebes Regency. The research gap lies in the limited empirical studies on SWOT-based development strategies for rural swimming pool tourism that integrate village tourism sustainability theory in peri-urban areas of Central Java. This study employed a descriptive qualitative approach with a single case study design. Data were collected through observation, in-depth interviews with seven informants, and documentation. The SWOT analysis yielded an IFAS score of 4.08 and an EFAS score of 4.23, positioning the business in Quadrant I (Growth Strategy), indicating potential for aggressive growth. Key strengths include natural mountain spring water, affordable pricing, and diverse attractions, supported by opportunities in family recreational tourism trends and digital promotion. The SWOT matrix produced 13 alternative strategies divided into SO, WO, ST, and WT strategies. Priority strategies include strengthening digital branding via Tiktok and Instagram, developing family tourism packages, and collaborating with BUMDes for facility improvement and management professionalism. This research contributes as an empirical reference for developing village tourism based on local potential in Indonesia.